Cardiac Biomarkers are Associated with Incident Fracture Risk in Advanced Chronic Kidney Disease - Aaltonen, Louise; Hellman, Tapio; Lankinen, Roosa; Hakamäki, Markus; Metsärinne, Kaj; Järvisalo, Mikko (SPRINGER, 2025)
Cardiovascular disease is associated with increased fracture risk in the general population. Few data exist on the association between cardiovascular health and incident fracture risk in patients with advanced CKD, a high-risk population for fractures. We aimed to assess the link between fracture risk and cardiovascular health in a prospective cohort of 210 patients with CKD stage G4-5. Incident fractures were recorded during a prospective follow-up of 5 years. Laboratory parameters, abdominal aortic calcification score, echocardiography, ultrasound assessment of brachial artery flow-mediated dilatation and carotid intima-media thickness, and maximal stress ergometry were obtained at baseline. A total of 51 fractures were observed in 40 (19%) patients during follow-up. In separate multivariable Cox proportional hazards models adjusted for age, gender, and baseline eGFR, TnT (HR 1.007, CI 95% 1.003-1.010, p < 0.001) and ProBNP (HR 1.000, CI 95% 1.000-1.000, p = 0.017) were associated with incident fractures and the association persisted after adjusting for coronary artery disease (CAD). The patients unable to perform the ergometry test had a higher risk of incident fractures compared to others (36.1% vs 15.5%, p = 0.009). A cardiovascular composite risk score summarizing TnT, ProBNP, and ergometry data was independently associated with incident fractures in a multivariable Cox model (HR 1.373, CI 95% 1.180-1.599, p < 0.001). Patients with the lowest score were observed with no fractures, while patients with the highest score were observed with a fracture risk of 40.5% during follow-up. Risk of incident fractures is associated with biomarkers of cardiovascular health and a composite cardiovascular risk score in patients with advanced CKD.